2019
DOI: 10.1111/1759-7714.13198
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of macrophage migration inhibitory factor expression in patients with squamous cell carcinoma of the lung

Abstract: BackgroundMacrophage migration inhibitory factor (MIF) has been shown to play an important role in the inflammatory and immune response in squamous cell carcinoma (SCC). Recent studies have reported that MIF is involved in the tumorigenesis and overexpressed in various cancers. In this study, we assessed the prognostic role of MIF expression in SCC of the lung, and demonstrated the effect of knockdown of MIF on the migration in lung SCC cell lines.MethodsThe relationship between MIF expression and clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…[ 10 ] Furthermore, MIF has been suggested as a potential prognostic factor for various cancers including gastric, hepatocellular, pancreatic, and lung cancers, and oral squamous cell carcinoma and metastatic melanoma. [ 3 , 7 , 8 ] Therefore, we conducted this meta-analysis to calculate the prognostic significance of MIF expression in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] Furthermore, MIF has been suggested as a potential prognostic factor for various cancers including gastric, hepatocellular, pancreatic, and lung cancers, and oral squamous cell carcinoma and metastatic melanoma. [ 3 , 7 , 8 ] Therefore, we conducted this meta-analysis to calculate the prognostic significance of MIF expression in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [ 11 ] showed that high expression of MIF was related with poor OS and metastasis-free survival in patients with high-grade osteosarcoma. Zhang et al [ 12 ] and Koh et al [ 8 ] demonstrated significantly poorer OS or disease-specific survival and DFS with high expression of MIF compared with low expression in patient with esophageal squamous cell carcinoma and lung squamous cell carcinoma, respectively. Kang et al [ 13 ] revealed the relationship between MIF expression and OS and recurrence-free survival in patients with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells secrete exosomes with intra-exosomal cargos, including tumor-suppressor genes, proteins, and other substances that might affect metastatic properties. To date, there have been many studies regarding the prognostic role of RAB27A and RAB27B through immunostaining methods in various cancer (12)(13)(14)(15)(16)(17)(18). In a previous study, we confirmed that RAB27A expression was strongly positive in a large group of patients with clearcell renal cell carcinoma (CCRCC) (13).…”
mentioning
confidence: 52%
“…[ 3 6 , 18 22 ] MIF is overexpressed in many solid tumors, including prostate, [ 23 ] hepatocellular, [ 24 ] gastric, [ 25 ] and adenocarcinoma and squamous cell carcinoma of the lung. [ 26 , 27 ] In most of tumors, the degree of MIF overexpression is positively correlated with tumor progression or metastatic potential. [ 8 ] It has been shown that neutralizing anti-MIF antibodies inhibit tumor angiogenesis in murine malignant lymphoma, [ 18 ] murine colon cancer, [ 19 ] and a human melanoma model.…”
Section: Discussionmentioning
confidence: 99%